Anesthesia Techniques and Long-Term Oncological Outcomes - Ramirez, Maria F.; Cata, Juan P. (Frontiers in Oncology, 2021)
Abstract Despite advances in cancer treatments, surgery remains one of the most important therapies for solid tumors. Unfortunately, surgery promotes angiogenesis, shedding of cancer cells into the circulation and suppresses anti-tumor immunity. Together this increases the risk of tumor metastasis, accelerated growth of pre-existing micro-metastasis and cancer recurrence. It was theorized that regional anesthesia could influence long-term outcomes after cancer surgery, however new clinical evidence demonstrates that the anesthesia technique has little influence in oncologic outcomes. Several randomized controlled trials are in progress and may provide a better understanding on how volatile and intravenous hypnotics impact cancer progression. The purpose of this review is to summarize the effect of the anesthesia techniques on the immune system and tumor microenvironment (TME) as well as to summarize the clinical evidence of anesthesia techniques on cancer outcomes